The Influence of Culture-Specific Personality Traits on the Development of Delinquency in At-Risk Youth. (April 2016) - Tong, Tat Seng; Ku, Lisbeth; Zaroff, Charles Mark
The association between culture-specific personality variables and family factors, and juvenile delinquency, was assessed in a sample of 402 adolescents of Chinese ethnicity between 12 and 17 years of age ( M age = 15.13, SD = 1.41; 135 girls), a subgroup of whom were considered at risk for juvenile delinquency owing to addictive behavior tendencies. Culture-specific personality variables were assessed using the Chinese Personality Assessment Inventory–Adolescent version Interpersonal Relatedness factor. The General Function subscale of the Chinese version of the Family Assessment Device was utilized to assess the influence of perceived levels of family functioning. Both culture-specific personality variables and non-culture-specific familial factors were significantly and negatively associated with self-reported juvenile delinquency ( p < .001). However, in a sample of at-risk adolescents, only a culture-specific variable measuring orientation toward the family was able to predict self-reported juvenile delinquency ( p < .001). Implications of the current results are discussed.